Unpacking Pretrial Detention: An Examination of Patterns and Predictors of Readmissions - Kim, Jaeok (Criminal justice policy review, 2018)
Pretrial detention makes up the majority of jail admissions, but little is known about this high-volume population. The current study fills this gap by examining the pretrial detention population in New York City and assesses their pretrial readmissions over a 10-year follow-up period. While the number of individuals detained pretrial has consistently decreased since 1995, the prevalence and the frequency of pretrial readmissions remain high: About 60% of the sample was readmitted at least once within 10 years and they were readmitted on average 3 times. A negative binomial model predicting readmission counts for felony and misdemeanor admissions found that males, non-Hispanic Blacks, and younger individuals were more frequently readmitted pretrial. Self-reported drug use and prior criminal records were associated with higher readmission counts. We also found that charge and discharge types predicted readmission counts. Findings suggest the importance of earlier intervention and developing targeted strategies to reduce further readmissions.